Metode PAR Sebagai Indikator Peningkatan Peran Masyarakat Terhadap Pengelolaan Limbah Plastik Dusun Paten Tridadi Sleman Yogyakarta - Ulfa Amalia; Dwi Ratnawati (Bagimu Negeri, 2017)
AbstractThe problem that develops today is rubbish management and is a serious indicator for potential environmental pollution, especially waste of household waste. The PAR approach leads people to take transformative actions that change the social conditions of better society. This dedication program can fulfill the external target of integrated plastic waste processing system, by increasing community participation through assistance, as well as intensive giving or sosialisation, the creation of plastic waste processing technology in the form of distillation, variety of the product are accessories and other handicraft products, ergonomic system, managerial system by utilizing garbage bank as waste processing place.  Keywords: Participatory Action Research, waste plastic management, community partisipation